Hydrogen Bonds: Simple after All? - Herschlag, Daniel; Pinney, Margaux M (Biochemistry (Easton), 2018)
Hydrogen bonds play integral roles in biological structure, function, and conformational dynamics and are fundamental to life as it has evolved on Earth. However, our understanding of these fundamental and ubiquitous interactions has seemed fractured and incomplete, and it has been difficult to extract generalities and principles about hydrogen bonds despite thousands of papers published on this topic, perhaps in part because of the expanse of this subject and the density of studies. Fortunately, recent hydrogen bond proposals, discussions, and debates have stimulated new tests and models and have led to a remarkably simple picture of the structure of hydrogen bonds. This knowledge also provides clarity concerning hydrogen bond energetics, limiting and simplifying the factors that need be considered. Herein we recount the advances that have led to this simpler view of hydrogen bond structure, dynamics, and energetics. A quantitative predictive model for hydrogen bond length can now be broadly and deeply applied to evaluate current proposals and to uncover structural features of proteins, their conformational restraints, and their correlated motions. In contrast, a quantitative energetic description of molecular recognition and catalysis by proteins remains an important ongoing challenge, although our improved understanding of hydrogen bonds may aid in testing predictions from current and future models. We close by codifying our current state of understanding into five “Rules for Hydrogen Bonding” that may provide a foundation for understanding and teaching about these vital interactions and for building toward a deeper understanding of hydrogen bond energetics.